Advanced Metasurface-Based Antennas: A Review - Wanchen Yang; Jinghao Li; Dongxu Chen; Yue Cao; Quan Xue; Wenquan Che (IEEE Open Journal of Antennas and Propagation)
As one kind of two-dimensional metamaterials, metasurface structures are widely applied in antennas due to the special abilities of manipulating the amplitude, phase, polarization states and the propagation modes of electromagnetic wave. This article briefly presents a series of combinations of metasurface and antennas from the perspective of design methods and innovative features, which are divided into three sections: performance improvement, function manipulation and other applications. In the section of performance improvement, three typical applications of metasurface are presented, including using non-periodic metasurfaces to raise aperture efficiency, introducing multi-mode resonance metasurfaces to expand bandwidth, and introducing capacitive loading metasurfaces for miniaturization. As for function manipulation, due to the high design freedom of metasurface, multi-polarization reconfigurability can be achieved by changing the surface impedance distribution. Moreover, it can be used as radiators and excited by traveling wave to achieve beam steering or combined with phase change materials to realize frequency reconfiguration. The last part is about the further applications of metasurface, including multi-folding reflectarray/transmitarray, wide-angle scanning phased array antenna, and filtering antenna. In conclusion, the researches of metasurface have overcome the shortcomings of conventional antennas and proposed some good solutions to realize innovative antennas.